The field of the beginnings of university life in Argentina: Contributions for its conceptual consolidation and its networked methodological approach (Revista de Estudios Teóricos y Epistemológicos en Política Educativa, 2025)
This essay analyzes the consolidation of the field of study at the beginnings of university life in Argentina, proposing it as a conceptual framework that surpasses the traditional notion of “admission.” Firstly, this field is reconstructed based on four key analytical dimensions: access policies, articulation between educational levels, pedagogical support, and the appropriation of academic culture. Secondly, given the complexity of this object of study, it is argued that isolated disciplinary approaches are insufficient. Within this framework, the case of the "Research Network on the Beginnings of University Life" (REIVU) is presented and analyzed as a methodological model of networked collaborative knowledge. The essay concludes that this federal and transdisciplinary way of working is a powerful epistemological tool for producing socially relevant and robust knowledge about access and persistence in higher education.Keywords: Beginnings of university life. Field of study. Collaborative knowledge.